THE USE OF TALKING CHIPS TECHNIQUE IN TEACHING SPEAKING - Syafryadin (2013)
This study investigated how the Talking Chips Technique can help students to improve their speaking. The sample of this study was only one class and total number of students was 36 students. This study used a quasi experimental design and three data collection, i.e. note taking, participant observation, and speaking test. The data from observation were analyzed by using thematic analysis and band score of speaking. This study was conducted by using multiple pre-test and post-test. Therefore, the findings of this study were based on pre- test, treatments and post- test. During the treatments, there were problems related to classroom management (noisy, low participation, laughing), fluency (pause, flow and speed) and accuracy (pronunciation, grammar and vocabulary). Those problems could be minimized. After post test, there were still problems, but the problems were fewer than previous ones like only fluency and accuracy because students had showed the awareness and enthusiastic in speaking English. This study showed the improvement of students' speaking achievement from treatment until post test. It was proved by the mean score pre test and post test. In pre-test, the mean score of fluency was 61.1 and 62.81 for accuracy. In post-test, the mean score of fluency was 71.451 and accuracy was 74.69. Then, t- test for fluency was 7.05 and t-test for accuracy was 8.31 with t critical or table was 2.031. It meant that H1 was accepted. It indicated that there was significance improvement of students' speaking in terms of fluency and accuracy. The findings above suggest that the students still need further treatments in order to improve their speaking even though they have achieved the target.